Revitalizing tetanus vaccine literacy post road accidents: a comprehensive examination of knowledge and awareness initiative among non-medical university students in Lahore, Pakistan - Ayub, Fiza; Saleem, Wahaj; Shahid, Muhammad Awais; Hussain Khan, Muhammad Afzal; Suleiman, Amal K.; Akram, Laiba; Sajid, Sadaf; Bukhsh, Allah; Baig, Mirza Rafi; Khan, Tahir Mehmood (Frontiers in Immunology, 2024)
IntroductionTetanus, caused by Clostridium tetani, poses a life-threatening risk by affecting the nervous system and inducing muscle tightness. The objective of this study is to examine the knowledge, attitudes, and behaviors of non-medical university students regarding the tetanus vaccine in the context of post-road accidents.MethodsA descriptive cross-sectional study was conducted in 2023, involving 378 students from non-medical disciplines, primarily from information technology, business administration, and engineering faculties, with a mean age of 20.7 years. The sample size was calculated using the Raosoft sample calculator, and participants were selected via consecutive random sampling. Data was collected through a structured, self-administered questionnaire and analyzed using SPSS 22.0.ResultsGender distribution was 51.6% female and 48.4% male. Out of the 378 students, 53.4% (p=0.003) were unaware of tetanus contraction sources, 52.8% (p=0.004) lacked knowledge of its symptoms and 68.3% (p=0.004) were unfamiliar with the total number of doses. An appreciable 88.9% (p0.063) are willing to receive post-accident tetanus vaccination, reflecting positive attitudes and openness to preventive measures. Similarly, the p-values >0.05 show no gender disparity in willingness to receive tetanus vaccination (p=0.063) and recommending vaccination to others after a road accident (p=0.879).ConclusionsNotwithstanding participants' positive attitudes, the results indicate poor knowledge of tetanus regarding its transmission, symptoms, and doses. Interventions should focus on refining practical aspects of education, including symptom recognition, vaccine efficacy, duration, and the importance of sustaining immunity.